Characterizing Low-Z erosion and deposition in the DIII-D divertor using aluminum. (August 2017) - Chrobak, C.P.; Doerner, R.P.; Stangeby, P.C.; Wampler, W.R.; Rudakov, D.L.; Wright, G.M.; Abrams, T.; Ding, R.; Elder, J.D.; Guterl, J.; Guo, H.Y.; Lasnier, C.; et al.
Highlights: Measured localized erosion and redeposition of Aluminum in DIII-D divertor plasmas. Modeled multi-step material migration across surfaces with different morphologies. Graphite surface roughness leads to enhanced accumulation of Al deposits. Experiments show asymmetry in re-deposition that is not reproduced by existing models. Abstract: We present measurements and modeling of aluminum erosion and redeposition experiments in separate helium and deuterium low power, low density L-mode plasmas at the outer divertor strike point of DIII-D to provide a low-Z material benchmark dataset for tokamak erosion-deposition modeling codes. Coatings of Al ∼100 nm thick were applied to ideal (smooth) and realistic (rough) surfaces and exposed to repeat plasma discharges using the DiMES probe. Redeposition in all cases was primarily in the downstream toroidal field direction, evident from both in-situ spectroscopic and post-mortem non-spectroscopic measurements. The gross Al erosion yield was estimated from film thickness change measurements of small area samples, and was found to be ∼40–70% of the expected erosion yield based on theoretical physical sputtering yields after including sputtering by a 1–3% carbon impurity. The multi-step redeposition and re-erosion process, and hence the measured net erosion yield and material migration patterns, were found to be influenced by the surface roughness and/or porosity. A time-dependent model of material migration accounting for deposit accumulation in hidden areas was developed to reproduce the measurements in these experiments and determine a redeposition probability distribution function for sputtered atoms.